Development and implementation of the mesh-free kp-RITZ method for the rotating shell dynamics - Zhao, Xin. (2008)
(This thesis consists of 2 sections) Aims to study the vibration and dynamic stability of cylindrical and conical shells, as well as the corresponding panels. The classical theory of thin shells is used and the mesh-free methodology is implemented for the vibration and dynamic stability analyses of cylindrical and conical shells/panels.